SYSTEMATIC LITERATURE REVIEW :ETHNOMATHEMATICS-BASED STUDENT WORKSHEET (LKPD) ON THE TOPIC OF SOLID FIGURES WITH FLAT SURFACES - Wayan Sri Jayantari; Yufitri Yanto; As Elly S (Universitas PGRI Silampari, 2025)
This article aims to examine the impact of using ethnomathematics-based student worksheets (LKPD) on the topic of three-dimensional shapes with flat surfaces in mathematics learning on students’ learning outcomes and to assess their mathematical problem-solving abilities. The method used in this study is a Systematic Literature Review (SLR). A total of 12 articles related to ethnomathematics-based LKPD on three-dimensional flat-surfaced shapes in mathematics learning from 2018 to 2024 were reviewed. These articles were sourced from Google Scholar and the Science and Technology Index (Sinta). The results of this Systematic Literature Review indicate that the use of ethnomathematics-based LKPD in learning can enhance students’ academic performance and improve their mathematical problem-solving skills.